Efektivitas Pemberian Jus Bayam Merah dan Pisang Ambon terhadap Kadar Hemoglobin Ibu Hamil - Syafitriya Ningsih; Dea Lestari; Cornetty Andryani Nura (Pusat Riset dan Inovasi Nasional, 2025)
Pregnancy is a unique natural condition because although it is not a disease, it often causes complications due to various anatomical and physiological changes in the mother's body. Pregnant women who suffer from anemia can have an impact on the fetus, such as premature birth, the risk of low birth weight (LBW), fetal abnormalities, and increased risk of fetal distress. In general, the causes of anemia in pregnancy are iron deficiency and acute bleeding or even the interaction of both. The purpose of this study was to determine the difference in the effectiveness of giving red spinach juice and Ambon bananas on Hb levels in pregnant women in the third trimester. The design used in this study was a quantitative inferential study including the pre-experimental type with two group pretest-posttest. Based on the time of data collection, it included the cross-sectional type, sourced from primary and secondary data. An assessment of the difference in increasing HB levels was carried out before and after treatment (Pretest and Postest two Group Design). Data analysis consisted of univariate and bivariate analysis. The results of the analysis showed an effect in giving red spinach juice and Ambon bananas. It is hoped that the Health Center will facilitate health workers (midwives) in providing information on providing guava juice with red spinach leaf juice as an alternative for preventing and managing anemia during pregnancy in the Health Center's work area.